Mexiletine for muscle cramps in amyotrophic lateral sclerosis: A randomized, double‐blind crossover trial. Issue 1 (6th April 2018) - Oskarsson, Björn; Moore, Dan; Mozaffar, Tahseen; Ravits, John; Wiedau‐Pazos, Martina; Parziale, Nicholas; Joyce, Nanette C.; Mandeville, Ross; Goyal, Namita; Cudkowicz, Merit E.; Weiss, Michael; Miller, Robert G.; et al.
ABSTRACT: Introduction : More than 90% of amyotrophic lateral sclerosis (ALS) patients have muscle cramps, but evidence‐based treatments have not been available. Methods : A multicenter, double‐blind, placebo‐controlled crossover trial of mexiletine 150 mg twice daily was conducted in ALS patients requesting treatment of symptomatic muscle cramps. Results : Muscle cramp frequency was reduced in 18 of 20 patients; 13 reductions were attributed to treatment ( P  < 0.05). The average reduction, based on t tests, was 1.8 cramps per day (a reduction from 5.3 with placebo to 3.5 with mexiletine). The estimated reduction of cramp severity was 15 units on a 100‐unit scale ( P  = 0.01) from a baseline average of 46. No effect on fasciculations was noted. One patient discontinued the study because of dizziness, and another patient discontinued the study to start open‐label mexiletine therapy. No serious adverse event occurred. Discussion : Mexiletine is a well tolerated and effective medication for controlling the symptom of muscle cramps in ALS. Muscle Nerve 58 : 42–48, 2018